Cover Image, Volume 7, Issue 6. (12th October 2017) - Gan, Wensheng; Lin, Jerry Chun‐Wei; Chao, Han‐Chieh; Zhan, Justin
Abstract : The cover image, by Wensheng Gan et al., is based on the Overview Data mining in distributed environment: a survey, DOI: 10.1002/widm.1216 . Abstract : The cover image, by Wensheng Gan et al., is based on the Overview Data mining in distributed environment: a survey, DOI: 10.1002/widm.1216 .